Age And Gender Differences In Body Fat Composition: A Cross-Sectional Study - Anung Putri Ilahika; Eduardo Pons-Fuster Lopez; Habib Saleh; Abi Noerwahjono (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2025)
Background: The increase in global obesity rates seems to be a consequence of changes in the global food system that lead to a shift in dietary patterns from traditional foods to fast food consumption. Increasing evidence from cross-sectional studies conducted around the world has shown that consumption of fast food is consistently associated with changes in body weight and obesity. The distribution of fat in different countries is influenced by genetic factors and external or environmental factors such as diet and physical activity. The results show that the Chinese have a higher body fat percentage than the Europeans. Genes are important factors that make up the human body, but the environment also plays an important role. This environment includes behavior or lifestyle patterns. Objective: To determine the effect of age and gender on body fat mass of UMM employees Methods: This research is an analytic observational study with the Cross Sectional method which was conducted to determine the effect of age and gender on fat mass in UMM employees. The total sample in this study was 50 employees. Data collection was carried out by filling out questionnaires and measuring using a microtoise and bioelectrical impedance analysis (BIA). Results: The results of the correlation test of age data on body fat mass found that there was no relationship between age and fat mass. Meanwhile, the influence of gender on body fat mass found a relationship between gender and body fat mass in employees of the University of Muhammadiyah Malang. Conclusion: There was no effect of age on body fat mass of UMM employees and there was an effect of gender on body fat mass of UMM employees.